2021
DOI: 10.1080/21655979.2021.2006551
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of integrin subunit alpha 11 restrains gastric cancer progression through phosphatidylinositol 3-kinase/Akt pathway

Abstract: Gastric cancer (GC) is among the most frequent malignancies originating from the digestive system worldwide, while the role and specific mechanism of integrin-subunit alpha 11 (ITGA11) in GC remain unclear. This study probes the expression characteristics and function of ITGA11 in GC. Firstly, the ITGA11 profile in GC tissues and paracancerous non-tumor tissues was assessed by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blot (WB), and the association between ITGA11 and GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Integrin α11 (ITGA11) is a known receptor for collagen. The role of this protein has been shown, especially in lung cancer and gastric cancer tissue, as being associated with tumor progression [ 25 , 27 ]. The extent to which it is involved in the induction of VLD needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrin α11 (ITGA11) is a known receptor for collagen. The role of this protein has been shown, especially in lung cancer and gastric cancer tissue, as being associated with tumor progression [ 25 , 27 ]. The extent to which it is involved in the induction of VLD needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the VLD patterns between different Fitzpatrick phototypes might be interesting to assess the protective effect of melanin. Another clinically interesting finding was the initial occurrence of VLD after CPI [ 11 , 13 , 27 ]. When analysing VLD onset, we found that patients who were pre-treated with targeted therapy had a significantly later onset: the median time to VLD onset was 12.5 months in the kinase-inhibitor pre-treated group vs. 6.25 months in the group without prior targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Itga11 has also been reported to be involved in PI3K/Akt and Wnt signaling pathway, supporting our findings from another view. ITGA11 is one of the core genes that could influence PI3K/Akt signaling pathway once they were activated 28 , its expression can affect tumor progression by modulating the PI3K/Akt pathway 29 . Besides, Wnt pathway can be activated by osteolectin/α11β1 signaling 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrin ITGB3 interacted with heparan sulfate proteoglycans (HSPGs) and assisted in integrin endocytosis, promoting the metastasis of breast cancer [ 7 ]. In GC, integrin subunit alpha 11 promoted gastric cancer cell proliferation and invasion and inhibited apoptosis through the phosphatidylinositol 3-kinase/Akt pathway [ 8 ]. Integrin, beta-like 1 (ITGBL1), also called ten β Integrin EGF-like repeat domains (TIED), encodes beta integrin-related extracellular matrix protein, which is highly similar to integrin β subunits.…”
Section: Introductionmentioning
confidence: 99%